Non-detergent isolation of a cyanobacterial photosystem I using styrene maleic acid alternating copolymers. Issue 54 (7th October 2019) - Brady, Nathan G.; Li, Meng; Ma, Yue; Gumbart, James C.; Bruce, Barry D.
Abstract : Trimeric Photosystem I (PSI) from the thermophilic cyanobacterium Thermosynechococcus elongatus (Te) is the largest membrane protein complex to be encapsulated within a SMALP to date. Abstract : Photosystem I (PSI) from the thermophilic cyanobacterium Thermosynechococcus elongatus (Te) is the largest membrane protein complex to have had its structure solved by X-ray diffraction. This trimeric complex has 36 protein subunits, over 380 non-covalently bound cofactors and a molecular weight of ∼1.2 MDa. Previously, it has been isolated and characterized in a detergent micelle using the non-ionic detergent n -dodecyl-β-d -maltoside (DDM). We have now succeeded in isolating this complex without the use of detergents, using styrene–maleic acid (SMA) alternating copolymer. Intriguingly, a partially esterified copolymer formulation (SMA 1440, Cray Valley) was found to be most efficient in cyanobacterial thylakoid membranes. A host of biochemical, biophysical and functional assays have been applied to characterize this non-detergent form of PSI, referred to as a SMA Lipid Particle (SMALP). The PSI-SMALP has a lower sedimentation coefficient compared to PSI-DDM, suggesting decreased density or a more extended particle shape. We show the 77 K fluorescence maximum for PSI is red shifted in PSI-SMALP compared to PSI-DDM, suggesting a more native orientation of PsaA/B associated chlorophyll. We report that PSI-SMALPs are functional despite the selective loss of one transmembrane subunit, PsaF. This loss may reflect a more labile interaction of the PSI core and PsaF, or a selective displacement during copolymer insertion and/or assembly. PSI-SMALP exhibited decreased reduction kinetics with native recombinant cytochromes c6, while non-native horse heart cytochrome c shows faster reduction of PSI-SMALP compared to PSI-DDM. This is the largest membrane protein isolated using SMA copolymers, and this study expands the potential use of this approach for the isolation and characterization of large supramolecular complexes.